Numerical analysis of the stress-strain state of laminated springs - Pestrenin, Valery Mikhailovich; Pestrenina, Irina Vladimirovna; Talantsev, Nikolay Filaretovich (Computational Continuum Mechanics, 2009)
This paper presents a procedure for numerical analysis of the stress-strain state of laminated springs under static loading conditions. The proposed procedure is based on the geometrically nonlinear elastic model of a deformable body. In contrast to the methods derived from the hypotheses of strength of materials, the present approach provides the fulfillment of real boundary conditions, description of actual contact interactions between the elements of the spring structure and investigation of its behavior taking account of forces contracting these elements and in the case of their interaction with the transport vehicle. An energetic criterion for the effective use of the material of the laminated spring is formulated. A comparative analysis of multi- and few-leaf springs used in transport vehicles is given. It is shown that application of few-leaf springs provides considerable metal saving compared to multi-leaf springs of similar functional parameters.